Menstrual cycle and situational match variables: Effects on well-being in professional female soccer players - Abbott, W.; Exall, Z.; Walsh, L.; Clifford, T. (Research Quarterly for Exercise and Sport, 2024)
Purpose We examined whether the situational match factors (location, result, and opposition quality), as well as playing position and menstrual cycle phase, influenced self-reported well-being in female soccer players.